2009
DOI: 10.4067/s0301-732x2009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical and pathological characteristics of 155 canines with mammary tumours: a retrospective study

Abstract: RESumEnEn este estudio se evaluaron en forma retrospectiva las características clínicas y patológicas de 155 perras con tumores mamarios. 55% de los animales con tumores mamarios eran Poodle (83 pacientes). La edad promedio al momento de la excisión del tumor fue de 10,3 ± 0,2 años, mientras que el tiempo transcurrido entre la detección del tumor y tratamiento del paciente fue de 308 ± 38,5 días. 46 de las 119 perras habían parido al menos una vez y 22 de 59 habían presentado un historial con falsa preñez. Ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
4
19
2
2
Order By: Relevance
“…One clinical study on dogs treated with medroxyprogesterone acetate for oestrus prevention reported a greater risk of developing mammary tumours, the majority being malignant. (16) In our study as well as in other studies (17,18) dogs were admitted in the clinic for examination and treatment, roughly a year after the fi rst detection of the mass. In our study 6 patients (66%) were with multiple mammary tumours.…”
Section: Discussionmentioning
confidence: 71%
“…One clinical study on dogs treated with medroxyprogesterone acetate for oestrus prevention reported a greater risk of developing mammary tumours, the majority being malignant. (16) In our study as well as in other studies (17,18) dogs were admitted in the clinic for examination and treatment, roughly a year after the fi rst detection of the mass. In our study 6 patients (66%) were with multiple mammary tumours.…”
Section: Discussionmentioning
confidence: 71%
“…The histological tumor type is an important factor for the survival of affected animals (Sontas et al, 2009). Mammary carcinomas in dogs have similarities with breast cancer in humans, including the high prevalence of adenocarcinoma, frequency of metastasis and progressive disease (Sartin et al, 1992).…”
mentioning
confidence: 99%
“…No entanto, o valor por eles encontrado para animais de pequeno porte, divergiu do estudo, que obteve resultado superior e apresentouse de acordo com Sontas et al (2009), os quais afirmam que tumores mamários malignos ocorrem comumente em fêmeas de pequeno porte, acometendo principalmente as glândulas mamárias inguinais, como ocorreu, neste estudo, em 61,53% dos casos avaliados de estádio IV e V. Ainda em relação às fêmeas de pequeno porte, observou-se, neste estudo, que 53,33% delas desenvolveram tumores menores que 3 cm, sendo que 75% eram de natureza invasiva, classificados em estádio IV, ao Ribas et al (2012) Archives of Veterinary Science, v.17, n.1, p.60-68, 2012.…”
Section: Methodsunclassified